2022
DOI: 10.3390/antibiotics11020129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dietary Probiotic Bacteria and Processed Yeast (GroPro-Aqua) as the Alternative of Antibiotics in Juvenile Olive Flounder Paralichthys olivaceus

Abstract: We investigated the three probiotic bacteria and a processed yeast (GroPro-Aqua) as the replacers of antibiotics in juvenile olive flounder. A total of seven diets were used, that is, one basal or control (CON) diet; and six other diets, of which, three diets were prepared by supplementing probiotic bacteria such as Bacillus subtilis WB60 (BSWB60) at 1 × 108 CFU/g diet, Bacillus subtilis SJ10 (BSSJ10) at 1 × 108 CFU/g diet, and Enterococcus faecium SH30 (EFSH30) at 1 × 107 CFU/g diet; one diet with processed y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…On the other hand, B. subtilis at 1 × 10 8 CFU g -1 with MOS did not show a significant 16 influence on the MPO activity of Japanese eel (Park et al 2020), suggesting that supplementation with the inclusion of B. subtilis at 1 × 10 7 CFU g -1 with MOS may be more effective for the Japanese eel. Interestingly, there was no significant difference in MPO activity of juvenile Olive Flounder (Paralichthys olivaceus) fed two strains of B. subtilis at 1 × 10 8 CFU kg -1 diet, E. faecium at 1 × 10 7 CFU g -1 , and an antibiotic-based diet (Choi et al 2022). Confirming earlier suggestions that the host-associated probiotics might be more effective, but an additional investigation is required (Ringø 2020).…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, B. subtilis at 1 × 10 8 CFU g -1 with MOS did not show a significant 16 influence on the MPO activity of Japanese eel (Park et al 2020), suggesting that supplementation with the inclusion of B. subtilis at 1 × 10 7 CFU g -1 with MOS may be more effective for the Japanese eel. Interestingly, there was no significant difference in MPO activity of juvenile Olive Flounder (Paralichthys olivaceus) fed two strains of B. subtilis at 1 × 10 8 CFU kg -1 diet, E. faecium at 1 × 10 7 CFU g -1 , and an antibiotic-based diet (Choi et al 2022). Confirming earlier suggestions that the host-associated probiotics might be more effective, but an additional investigation is required (Ringø 2020).…”
Section: Discussionsupporting
confidence: 70%
“…The feed additives used in this experiment were a control (CON) without additive supplementation, taurine (TW, 0.5%), peptide (PT, 0.3%), mineral water (MW 0.217%), Gro-pro ® (GRO 0.35%), Gro-pro + taurine (GRO + TW 0.35% + 0.5%), Gro-pro + peptide (GRO + PT 0.35% + 0.3%), Gro-pro + mineral water (GRO + MW 0.35% + 0.217%) and oxytetracycline (OTC 0.5%). The dietary inclusion levels of four feed additives were based on previous studies, such as Choi et al [ 36 ] for Gro-pro ® (GroPro Aqua, Angel Yeast Co. Ltd., Yichang, China), which is a yeast-derived protein and nucleic acid-based commercial feed additive used as a growth and palatability enhancer in aquaculture, and Kim et al [ 25 ] and Jo et al [ 27 ] for taurine. Additionally, according to the manufacturer’s recommendation, peptide, which is rich in peptide, nucleotide, glutamic acid, amino acids and inositol (NuPro, Alltech Inc., Seoul, Republic of Korea), and laboratory-made mineral water (consisting of 95% water and 5% minerals such as Ca, P, Na, K, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, IMP and SSE were found to be easily obtainable from waste valorization processes, which would be economically feasible and involve fast production at lower costs. In a recent study, Choi et al [ 36 ] found that a dietary yeast-extracted nucleotide with probiotics could replace antibiotics in terms of improving growth, immunity, gut health and disease resistance in juvenile olive flounder. These single-cell protein meals have a remarkably high protein content, with a well-balanced essential amino acid profile that does not compromise growth performance, and improve gut health and reduce enteritis associated with high-soybean feeds without being detrimental to the growth, antioxidation or immunity of fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of infection, chemotherapies are usually prescribed to relieve the impacts of A. hydrophila infection on common carp [ 8 ]. Although fish farmers are currently using some antibiotics for the treatment/control of this bacterial disease, a continuous supply of antibiotics can enhance bacterial resistance, environmentally hazardous factors, and food safety issues [ 9 , 10 ]. Hence, antibiotics may be substituted with ecologically safe feed additives such as probiotics/prebiotics, seaweeds, and herbal drugs [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%